Detection of rotavirus in diarrhoeic calves in Malaysia by electron microscopy - Abdul Rahman, Sheikh Omar; Ibrahim, A. L. (S. Karger, 1984)
Faecal samples of 80 diarrhoeic calves in 3 age groups were examined under the electron microscope for presence of virus and subjected to routine bacteriological examination for enterobacteria. Twelve samples (15 %) revealed the presence of typical rotavirus with the majority of them (67%) occurring in calves younger then 3 months. Minute particles resembling parvo- or enterovirus were observed in 12 other samples (15%). No significant pathogenic bacteria were isolated.